Modulation of Valley Dynamics in Hybrid H/T Phase Monolayer WSe2. Issue 1 (19th October 2022) - Liu, Haiyang; Zheng, Xuanli; Liu, Gaohong; Yin, Jun; Ke, Congming; Yang, Weihuang; Wu, Yaping; Wu, Zhiming; Li, Xu; Zhang, Chunmiao; Xu, Feiya; Kang, Junyong
Abstract: Two unequal K and K' valleys in transition metal dichalcogenides (TMDC) enable large and controllable polarization, which is the cornerstone of emerging valleytronic applications. Here, a phase engineering strategy aided by resonant plasmonic coupling is proposed to manipulate the valley degree of freedom. Compared with the pristine WSe2 monolayer, the hybrid H/T phase WSe2 exhibits an enhanced degrees of circular polarization (DCP) and valley polarization (DVP). As further aided by the designed Au plasmonic array, the T phase facilitates the excitons process and promotes the charge transfer in WSe2 /Au interface under the plasmonic‐enhanced electromagnetic field. Consequently, both the DCP and DVP values are considerably enhanced to 38.5% (15.6%) and 15.1% (7.6%) at 13 K (room temperature), respectively. Through finite difference time domain simulations (FDTD), the near‐field excitation, exciton decay, and far‐field detection processes are systematically analyzed, and highly consistent polarizations are quantitatively achieved between the theoretical and the experimental results. Accordingly, the high polarizations are revealed to be contributed by the increased exciton generation and radiation efficiency, chiral electromagnetic field, and non‐equilibrium spin distribution in the hybrid phase. The research presented here illustrates a promising route to control the spin and valley degrees of freedom in TMDC materials. Abstract : The valley degree of freedom in monolayer WSe2 is modulated through phase engineering aided by chiral plasmonic coupling. The degrees of circular polarization and valley polarization are considerably enhanced to 38.5% and 15.1%, respectively.